2021
DOI: 10.1177/00034894211054948
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Rhinosinusitis Outcomes of Patients With Aspirin-Exacerbated Respiratory Disease Treated With Budesonide Irrigations: A Case Series

Abstract: Background: Pathophysiology-targeting treatments exist for aspirin-exacerbated respiratory disease (AERD) through aspirin desensitization and biologics, such as dupilumab. With increasing attention paid to these treatments, which may be associated with significant side effects and/or cost, there is little description of chronic rhinosinusitis with nasal polyps (CRSwNP) response to treatment with intranasal corticosteroids and saline irrigations in AERD. Objective: To determine the effect of intranasal budesoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Rotenberg et al [23] could not identify any differences between the use of HSNR and saline rinses alone. Talat et al [31] found a reduction in SNOT-22 and nasal polyps score, but the study was not placebo controlled.…”
Section: Snidvongs Et Al'smentioning
confidence: 93%
See 3 more Smart Citations
“…Rotenberg et al [23] could not identify any differences between the use of HSNR and saline rinses alone. Talat et al [31] found a reduction in SNOT-22 and nasal polyps score, but the study was not placebo controlled.…”
Section: Snidvongs Et Al'smentioning
confidence: 93%
“…Regarding the type of steroid, 15 studies used budesonide [6,13,14,16,18,[21][22][23][24][25][27][28][29][30][31], 2 mometasone [15,20], 1 fluticasone [26], and 1 bethametasone [13,17].…”
Section: Question 3: Which Treatment Modality Is Better?mentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 In the last years, few studies have evaluated these objectives from therapeutic (antileukotriene therapy, nebulized steroids, and aspirin desensitization) and surgical maneuvers on sinus outcomes in a second time with variable results. [11][12][13][14] However, the use of standard therapy for asthma control in N-ERD long-time has not been sufficiently described, has only been described that the combination of ICS plus long-acting β2-agonists (LABA, ICS/LABA) and antileukotrienes diminishes bronchial symptoms during aspirin oral challenge in N-ERD patients. 15 N-ERD has been considered a severe asthma phenotype for many years, 16 requiring the use of multiple medicines or large doses for asthma control.…”
Section: Introductionmentioning
confidence: 99%